IMAGE OF A CIRCASSIAN WOMAN IN THE WORKS OF ADYGHE ENLIGHTENERS - Kumahova, Zairat Hasanbievna; Konovalov, Andrej Anatol'evic; Tekueva, Madina Anatol'evna (History, Archeology and Ethnography of the Caucasus, 2024)
In recent decades, the modern domestic research field has expanded significantly with the emergence of new directions, including the study of problems that previously did not attract historians’ attention. One rapidly developing approach in historical science is gender history. This article explores the image of the Circassian woman in the works of the Adyghe enlighteners of the 19th century, focusing on the male perspective of women, their place, and role in society. While the legacy of the Adyghe enlighteners – spanning scientific, literary, political, social, and economic views – has been extensively studied by Caucasian scholars, a shift towards gender studies offers a new assessment of their work. Using the phenomenological approach as a theoretical and methodological basis, the study aims to reconstruct the image of the “ideal” Circassian woman as envisioned by the Enlightenment, rather than her actual position in Adyghe society. It is argued that the Circassian intellectual elite’s perception of women’s place and role in traditional society was influenced equally by two factors: the patriarchy embedded in Circassian cultural codes and the contrasting romantic Russian tradition that shaped their worldview. The factual material, including ethnographic works and artistic creations by the Adyghe intellectual elite, provides insights into both the objective reality of Circassian women’s lives and the subjective literary depictions of female characters by the enlighteners. This research approach elucidates the often-contradictory views of the Adyghe educators on women. Notably, Adyghe enlighteners significantly contributed to creating the stereotypical image of a Circassian woman –characterized by feminine beauty, honor, pride, reverence for parents, and love for the Motherland – a depiction that has become prevalent in historical science and fiction.